A review of dupilumab in the treatment of atopic diseases - Quinn Thibodeaux; Mary Patricia Smith; Karen Ly; Kristen Beck; Wilson Liao; Tina Bhutani (Taylor & Francis Group, 2019)
Dupilumab is a fully human monoclonal IgG4 antibody directed against the alpha subunit of the IL-4 receptor and prevents the signaling of IL-4 and IL-13, two type 2 cytokines known to be important drivers of atopic diseases. In March of 2017, the United States Food and Drug Administration (FDA) approved dupilumab for the treatment of moderate-to-severe atopic dermatitis in adults that is uncontrolled with topical medications, becoming the first biologic agent approved to treat this chronic skin condition. In October of 2018, Dupilumab received approval by the FDA as an add-on maintenance therapy in patients with moderate-to-severe asthma aged 12 years or older with an eosinophilic phenotype or with oral corticosteroid-dependent asthma. This review summarizes the characteristics of dupilumab and the clinical research that has been published to date, including treatment efficacy and adverse events.